KOMUNIKASI PERSUASIF ORANG TUA DALAM MENGAJAK ANAK USIA DINI UNTUK MELAKSANAKAN SHOLAT FARDHU DI DESA PANCURAN GADING KECAMATAN TAPUNG KABUPATEN KAMPAR - Kuswara "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Muslims are obliged to pray because it is a pillar of religion. It is the duty of parents to teach and invite children to perform fard prayer from an early age. For that parents use persuasive communication in order to be able to change the attitudes, behaviors, and actions of children towards better according to the wishes of parents. The purpose of this study was to find out the characteristics, the message conveyed, the media used by parents in inviting early childhood to perform fard prayer in Pancuran Gading Village, Tapung District, Kampar District. This study uses a qualitative method, where the selection of informants uses accidental techniques, namely interviewing parents and children who are encountered during prayer fardhu in the mosque. To get the desired data, the researcher made observations first, followed by informant interviews and documentation. Analyzing the data obtained using Huberman and Miles data analysis techniques, the Interactive Data Analysis Model consists of four stages: data collection, data reduction, data display, conclusion / verification. To achieve the validity of the data, researchers used an extension of participation and triangulation. The results showed that the characteristics possessed by parents were credibility, attractiveness, and power. Credibility is seen from experience, educational background, sincerity and patience of parents. The personality of parents who can know the desires of children by making a good approach so that they are liked by children becomes the attraction of parents in the eyes of children. Gift giving is like mukenah with cartoon characters and advice needed when children ignore the five daily prayers. The message conveyed by parents in the form of verbal, namely with words or simple language, used in everyday life so that it is easily understood by children and nonverbal in the form of gestures, friendly facial expressions, and low tone of voice. To support persuasive communication so that it runs smoothly, parents use face-to-face media and television as supporting media.  Keywords:      Persuasive Communication, Parents, Early Chidhood, Prayer.